DYNAMICS OF THE FINANCIAL-BANKING SECTOR DEVELOPMENT OF UZBEKISTAN FOR THE YEARS 2017-2024 - Shovkatov Nodirjon Ne’matjon ugli; Namozova Maftuna Utkirovna (Journal of Artificial Intelligence and Digital Economy, 2024)
Analyzing the dynamics of the development of the financial-banking sector of Uzbekistan from 2017 to 2024, this article conducts an in-depth examination of key trends, factors, and changes shaping its contemporary landscape. Attention is devoted not only to macroeconomic reforms and government strategic initiatives but also to the penetration of digital technologies into the financial sphere, as well as the sector's response to global economic challenges such as the COVID-19 pandemic. Additionally, the article explores structural changes in the banking system, including the emergence of new market players, mergers and acquisitions, and regulatory adjustments. The main objective of the work is to provide readers with a profound understanding of how Uzbekistan's financial-banking sector has evolved in recent years and what prospects lie ahead, delineating key trends and development directions.